Validasi Instrumen Illinois Bully Scale (IBS) Untuk Mendeteksi Tingkat Bullying di SMAN 3 Malang - Bariyyah, Khairul; Very Andriyas, Ardi Nurwanda; Hotimah, Chusnil; Ansorullah, Evan Falyakun; Lathifa, Fatimah Rahmaniar; Nisa, Ica Sidatun; Kholifah, Siti; Laili Budiyono, Alief; Maizura, Nining (Indonesian Institute for Counseling, Education and Theraphy, 2024)
Bullying is a common issue in the school environment, with negative impacts on the mental health of individuals who become victims. To provide appropriate intervention, an instrument is needed to understand the initial conditions in the field. This step is taken to identify the level of bullying occurring in schools. Counselors require an initial assessment using an instrument to determine the level of bullying in schools. Therefore, the purpose of this study is to develop the Illinois Bully Scale (IBS) instrument to detect the initial level of bullying in high schools.This study involves several steps. First, content validity was assessed by three guidance and counseling experts who evaluated the suitability and relevance of the instrument items to the measurement objectives. Expert assessments indicated that the instrument was deemed appropriate with suggestions and improvements. Second, construct validity was tested using Confirmatory Factor Analysis (CFA) to verify whether the instrument items correspond to the expected factors. Criterion validity was also measured by examining the correlation between the IBS results and other relevant scales. Reliability testing was conducted by calculating Cronbach's Alpha.The study subjects were students from SMA Negeri 3 Malang, with a sample of 109 students from grades 10, 11, and 12. The study results indicate that this instrument is valid and reliable, with each statement item scoring above 0.8 in the analysis. Future researchers are encouraged to design interventions to address the issue of bullying in schools.